Analisis Teknik Bermain Futsal Timnas Futsal Putra Indonesia Pada Kualifikasi Piala Asia Futsal 2024 - Ruben Salvador Putra Panggalaha; Abdul Aziz Hakim; Achmad Widodo; Mokhamad Nur Bawono (STIKes Ibnu Sina Ajibarang, 2024)
Futsal has the goal of winning by scoring as many goals as possible against the opponent's goal. Tactics are needed to achieve this. Playing techniques are something that must be mastered to become a winner. The AFC (football and futsal association) on the Asian continent held the AFC Futsal Championship 2024 tournament. Qualifications were held to screen the number of participants. The purpose of this study was to determine the level of playing technique skills of the Indonesian men's futsal national team when participating in this tournament. The method used in this research is descriptive quantitative. The data source of this research comes from video replays of the Indonesian men's futsal national team matches uploaded by the Indonesian Futsal Federation (FFI) on their official YouTube channel. The results of this study found that in the match against Macau the number of passing of the Indonesian men's futsal national team reached 573 times with a success percentage of 93%, control reached 489 times with a success percentage of 97%, chipping 13 times with a success percentage of 54%, dribbling 144 times with a success percentage of 92%, and shooting 79 times with a success percentage of 63%. Against Afghanistan passing reached 548 times with a success percentage of 91%, control 502 times with a success percentage of 97%, chipping 33 times with a success percentage of 48%, dribbling 200 times with a success percentage of 95%, shooting 33 times with a success percentage of 58%, and powerplay 19 times with a success percentage of 11%. Against Saudi Arabia passing reached 434 times with a success percentage of 90%, control 370 times with a success percentage of 98%, chipping 31 times with a success percentage of 32%, dribbling 174 times with a success percentage of 91%, shooting 36 times with a success percentage of 58%, and powerplay 12 times with a success percentage of 8%.